85-Year-Old Postsurgical Complex Patient Successfully Managed Remotely at the Novel Mayo Clinic's Hospital at Home. (25th February 2022) - Paulson, Margaret R.; Torres-Guzman, Ricardo A.; Avila, Francisco R.; Maita, Karla; Garcia, John P.; Eldaly, Abdullah; Palmieri-Serrano, Luiza; Forte, Antonio J.; Thompson, Jonathan C.; Maniaci, Michael J.
Abstract : An 85-year-old male presented to the podiatry clinic following a 1st to 5th left toe amputation as a complication of severe peripheral arterial disease and nonhealing wound despite endovascular intervention with an angiogram. At the visit, cellulitis with gangrene of the surgical site was noted. The patient was admitted to the brick and mortar (BAM) hospital and taken to surgery for a transmetatarsal amputation of the left limb. In the immediate postoperative period, the incisional margins appeared dusky creating concern for flap viability. The medical team recommended a vascular bypass versus a below-knee amputation. However, given the age, comorbidities, and nutritional status, the family refused further surgical intervention. As such, Mayo Clinic's home hospital program, Advanced Care at Home (ACH), was consulted for continued nonsurgical acute management at home. The patient was transferred to ACH and transported home three days after BAM admission to continue IV antibiotic therapy and wound care. Discharge from ACH occurred 11 days after admission to the BAM hospital. This case highlights the importance of developing health care alternatives to traditional hospitalization and demonstrates that ACH can manage highly complex, elder postoperative patients from the comfort of their homes.